2009
DOI: 10.1111/j.1439-0310.2009.01642.x
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Geographic Song Preferences in Female Song Sparrows Melospiza melodia

Abstract: Previous work suggests that early learning plays a role in auditory preferences of female songbirds. We explored whether early experience shapes preferences for local geographic song in female song sparrows (Melospiza melodia), a species that prefers local geographic song in adulthood. We hand‐reared females from two locations 450 km apart and controlled song exposure early in life. To examine the effects of experience and inherited factors on geographic song preferences, we used a counterbalanced design. Fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Therefore, reciprocal translocations of adult birds (possibly ≥ 100) might be required to create territorial openings at the respective sites. Several studies in other songbirds show that female birds also prefer familiar song over unfamiliar song (Searcy et al 1997; O’Loghlen and Beecher 1999; Patten et al 2004; Hernandez et al 2009) but such studies are rarer, and exceptions have been reported (Nelson and Soha 2004a). Translocation of eggs or chicks for local song tutoring might also be viable management options but will be expensive logistically and ethically challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, reciprocal translocations of adult birds (possibly ≥ 100) might be required to create territorial openings at the respective sites. Several studies in other songbirds show that female birds also prefer familiar song over unfamiliar song (Searcy et al 1997; O’Loghlen and Beecher 1999; Patten et al 2004; Hernandez et al 2009) but such studies are rarer, and exceptions have been reported (Nelson and Soha 2004a). Translocation of eggs or chicks for local song tutoring might also be viable management options but will be expensive logistically and ethically challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that birds can distinguish geographical variation in song (Nelson and Soha 2004b; Podos 2007), typically by measuring the response of males to playback of geographical song variants, but also of females (O’Loghlen and Beecher 1999; Hernandez et al 2009) or pairs (Searcy et al 1997; Nelson and Soha 2004a; Patten et al 2004). However, an understanding of how rapidly this perceptual discrimination evolves is lacking (Zuk and Tinghitella 2008).…”
mentioning
confidence: 99%
“…they are exposed to when young, but do not replicate tutor song and thus do not experience sensorimotor learning. However, female songbirds do reference the song memories they form early in life when assessing songs they hear as adults (Clayton, 1990;Nagle and Kreutzer, 1997;Riebel, 2000;Hernandez and MacDougall-Shackleton, 2004;Hernandez et al, 2009;Anderson et al, 2014). Developmental conditions can impact brain structure and function underlying these learning processes, resulting in life-long effects on behavior that are correlated with the relative vulnerability of underlying neural systems (Nowicki et al, 2002a;Pravosudov et al, 2005;Buchanan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Females of various species have been found to prefer longer songs (Eens et al, 1991;Wasserman and Cigliano, 1991), more complex songs (Clayton and Pr€ ove, 1989;Spencer et al, 2005), larger song repertoires (Searcy, 1984;Hasselquist et al, 1996), and songs that were copied more accurately from tutors (Nowicki et al, 2002b). Females also have been shown to prefer songs similar to those they heard early in life (Clayton, 1990;Nagle and Kreutzer, 1997;Riebel, 2000;Hernandez and MacDougall-Shackleton, 2004;Hernandez et al, 2009;Anderson et al, 2014;Lachlan et al, 2014), suggesting that females learn songs when young and reference those memories when making mate choice decisions (Catchpole, 1980;Wasserman and Cigliano, 1991;Gentner and Hulse, 2000;Gil and Gahr, 2002;Riebel et al, 2002;Riebel, 2003). Thus, female songbirds likely undergo a learning process that could be impacted by developmental conditions, ultimately influencing their mate choice behavior (MacDonald et al, 2006;Riebel et al, 2009;Woodgate et al, 2010;Schmidt et al, 2013;Farrell et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In their review, Byers and Kroodsma (2009) found that field studies showed less support for the repertoire size hypothesis than did lab studies, and that opposing results were obtained for 8 of 12 species with multiple studies. Furthermore, the two hypotheses may not be mutually exclusive, as female birds of some species prefer locallyshared songs (O'Loghlen and Rothstein 1995;O'Loghlen and Beecher 1999;Hernandez et al 2009) or prefer males who are dominant in countersinging interactions (Mennill et al 2002).…”
Section: Introductionmentioning
confidence: 99%